Kualitas Fisik Telur Puyuh Yang Direndam Dalam Larutan Gelatin Tulang Kaki Ayam Dengan Lama Penyimpanan Yang Berbeda - Indra Joni (Jurnal Peternakan, 2017)
Quail eggs is one of the perishable food. If left in the open air at room temperature, the shelf life ranged between 10-14 days. Preservation is one of the way to prolong shelf life which can be done by soaking the eggs in a gelatin solution. The purpose of the study was to know the physical quality of quail egg soaked in gelatin bone chicken feet long with different time of storage. The experimental design of this study was Complete Randomized Design (CRD) factorial pattern 3 x 3 with 5 replications. The first factor was soaking time (0, 30 and 60 minutes) and the second factor was storage time (0, 15 and 30 days). The results showed that there was nos ignificant effect of soaking period (P>0.05) on egg weight, egg white index, yolk index, Haugh units and pH. The longer the storage time, the egg weight, egg white index, yolk index, haugh unit were decreased and the other hand, pH value was increased. Soaking quail eggs in gelatin solution of chicken feet during 30 minutes and storage time for 15 days resulted in pH value almost the same with untreated egg(control).